Virtual reality-based eye examination at a community-free clinic: A pilot study - Jullian Valadez; Howard Zhang; Sylvia L. Groth (Journal of Clinical Ophthalmology and Research)
Aims: This study aims to implement a comprehensive virtual reality (VR) eye examination at a free clinic and to compare its accuracy, time efficiency, and patient satisfaction to the manual examination. Settings and Design: Prospective pilot study. Materials and Methods: Adult patients attending a monthly clinic underwent standard examination followed by VR visual acuity (VA), visual field (VF), extraocular movements (EOM), pupillometry, and Ishihara testing. The tests were timed, and patient preferences were surveyed. Statistical Analysis Used: Mann–Whitney U-test for examination duration, Wilcoxon signed-rank test for patient preferences, and intraclass correlation analysis for VA results. Results: Fifty eyes across 25 participants were included. The participants were mostly female (84%) with a median age of 52 years (interquartile range [IQR] 12), and the majority spoke Spanish as their primary language (68%). The VR examination (median 6.61 min, IQR 3.35), excluding 3 min of tutorials, was significantly faster than the manual examination (median 17 min, IQR 9.5, P < 0.001). The VR far VA results positively correlated with the manual examination (intraclass correlation coefficient 0.628, P < 0.001). The VR VF, EOM, pupil, and Ishihara color test results matched the manual examination (no abnormal findings were missed). Eighty-two percent of survey participants preferred the VR examination, which received high ratings in physical comfort (mean 4.45/5, standard deviation [SD] 0.89) and interface (mean 4.55/5, SD 0.84) as compared to the manual examination (mean 4.14/5, SD 0.92, P = 0.074). Conclusions: Our study identified a VR-based examination that increased the scope of ocular testing, efficiency, and patient satisfaction in a free clinic.